2020
DOI: 10.3389/fmicb.2020.01284
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Salt Solution Parameters Limit the Survival of Planococcus halocryophilus in Martian Cryobrines

Abstract: Microorganisms living in sub-zero environments can benefit from the presence of dissolved salts, as they significantly increase the temperature range of liquid water by lowering the freezing point. However, high concentrations of salts can reduce microbial growth and survival, and can evoke a physiological stress response. It remains poorly understood how the physicochemical parameters of brines (e.g. water activity, ionic strength, solubility and hydration shell strength between the ions and the surrounding w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Furthermore, chaotropicity, a value describing the entropic disordering of biomacromolecules like proteins or lipid bilayers, has been described as a major biological stressor in many environments [13][14][15]. In addition, the size and strength of hydration shells around the solutes may influence membrane permeability and, consequently, affects the toxicity to organisms [16,17]. Other solute-specific parameters may influence the toxicity as well [17], such as interaction with metabolic processes, changes of pH or an enhanced redox potential of the solutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chaotropicity, a value describing the entropic disordering of biomacromolecules like proteins or lipid bilayers, has been described as a major biological stressor in many environments [13][14][15]. In addition, the size and strength of hydration shells around the solutes may influence membrane permeability and, consequently, affects the toxicity to organisms [16,17]. Other solute-specific parameters may influence the toxicity as well [17], such as interaction with metabolic processes, changes of pH or an enhanced redox potential of the solutes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the size and strength of hydration shells around the solutes may influence membrane permeability and, consequently, affects the toxicity to organisms [16,17]. Other solute-specific parameters may influence the toxicity as well [17], such as interaction with metabolic processes, changes of pH or an enhanced redox potential of the solutes.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies concluded that physicochemical properties such as ionic strength and water activity alone did not determine the limits of growth, instead the combination of anions and cations also had an effect on bacteria. Waajen et al ( 2020 ) also indicated that anion properties were among the most important parameters that affected the survival of a Planococcus halocryophilus strain at extremely low temperature values when comparing brine solutions of nine different salts, while Banciu et al ( 2004 ) observed higher biomass yield of a Thialkalivibrio halophilus strain in NaCl than in Na 2 CO 3 , and hypothesized that the adaptation to high salinities could, at least partly, be explained with differences in the osmotic pressure caused by these salts at equal sodium ion concentration (4 M). Contrary to these experiments performed on individual bacterial strains, to the best of our knowledge, systematic study on the effect of different dissolved ions on a large set of bacteria isolated from different saline lakes like ours (i.e., 172 bacterial strains isolated from 6 different lakes in 3 different regions and tested on 3 different salts) has not been carried out before.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 2, 2022. ; https://doi.org/10.1101/2022.05.02.490276 doi: bioRxiv preprint 3 permeability through variations in ionic hydration shells (9). Some anions like perchlorate additionally evoke chaotropic stress (10), i.e., they destabilize biomacromolecules like proteins, presumably through nonlocalized attractive dispersion forces (11).…”
Section: Introductionmentioning
confidence: 99%